European Review of Aging and Physical Activity - Netz, Yael; Zijlstra, Wiebren; Brach, Michael
European Review of Aging and Physical Activity (EURAPA) disseminates research on the biomedical and behavioural aspects of physical activity and aging. The main issues addressed by EURAPA are the impact of physical activity or exercise on cognitive, physical, and psycho-social functioning of older people, physical activity patterns in advanced age, and the relationship between physical activity and health.